A neodymium iron boron magnet and its preparation method and application

By growing the first and second grain boundary phases in the neodymium iron boron magnet and controlling the content of B, Ga, Cu and aging treatments, the problem of high cost and low B content of heavy rare earths in the prior art is solved. Neodymium iron boron magnets with high coercivity and high temperature stability are achieved, reducing production costs.

CN118919201BActive Publication Date: 2024-12-13BEIJING ZHONG KE SAN HUAN HI TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411412584.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-13
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the prior art, in order to improve the coercive force and high temperature performance of sintered NdFeB magnets, it is usually necessary to add high-cost heavy rare earth elements, and the R2T17 phase will be formed at low B content, resulting in a decrease in magnetic performance, making it difficult to not add heavy rare earths. Meet high-temperature performance requirements in the case.

Method used

By growing more first and second grain boundary phases in the neodymium iron boron magnet, the T element, especially the Fe element, is concentrated in the grain boundary phase of the triangular region, and the T element content in the thin layer grain boundary phase is reduced. , improve anti-demagnetization ability and temperature stability, and adjust the content of B, Ga, Cu and aging treatment temperature to build an appropriate tissue structure to consume iron and increase the coercive force of the magnet.

Benefits of technology

It is realized that the coercive force and high temperature stability of neodymium iron boron magnets are improved without adding heavy rare earth elements, and the production cost is reduced. The Br and Hcj performance of the magnets reaches 13.16kGs and 20.06 kOe or above, 20-180℃Hcj The temperature coefficient is within 0.565, meeting the high-temperature performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118919201B_ABST
    Figure CN118919201B_ABST
Patent Text Reader

Abstract

The present invention provides a NdFeB magnet and a preparation method and application thereof, wherein the composition of the NdFeB magnet includes R, M, a remainder T and inevitable impurities, wherein the T includes Fe; the R includes any one of Nd, Pr, La, Ce or Y or a combination of at least two; the M includes any one of Cr, Co, Ni, Ga, Cu, Ti, Al, Zr or Nb or a combination of at least two; the organizational structure of the NdFeB magnet includes: R2T14B main phase grains, a thin layer grain boundary phase and a triangular grain boundary phase; the triangular grain boundary phase includes a first grain boundary phase and a second grain boundary phase; the R content in the first grain boundary phase is less than 30at%, and the R content in the second grain boundary phase is greater than 30at%; on any cross section of the magnet, the area of ​​the first grain boundary phase accounts for 65-86% of the total area of ​​the triangular grain boundary phase. The present invention can obtain a sintered NdFeB magnet with both high remanence and coercivity, which meets the current application requirements for high temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnets, and in particular to a neodymium iron boron magnet and a preparation method and application thereof. Background Art

[0002] Sintered NdFeB magnets are widely used in many fields such as automotive industry, electronic products, wind power, elevators, industrial robots and aerospace due to their excellent magnetic properties. The demand for them is increasing, and the requirements for magnet performance, remanence and coercive force performance are also getting higher and higher.

[0003] In order to improve the remanence of sintered NdFeB magnets, it is usually necessary to reduce the B content in the magnets. However, when the B content is low, the R2T17 phase will be formed, which will reduce the magnetic properties of the magnets.

[0004] In the prior art, in order to meet the high temperature performance requirements of magnets, the coercivity of magnets is generally increased by directly adding heavy rare earth elements or by using grain boundary diffusion of heavy rare earth elements. However, heavy rare earth elements are expensive and the production cost is high.

[0005] Therefore, how to increase the coercivity of low B content sintered NdFeB magnets and improve the temperature coefficient of the magnets to meet the current demand for high temperature performance without adding heavy rare earths as much as possible is a difficult problem that needs to be solved urgently. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a NdFeB magnet and a preparation method and application thereof, which can improve the comprehensive magnetic properties of the NdFeB magnet without adding heavy rare earth elements and reducing the B content, and has excellent high temperature performance and broad application prospects.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a NdFeB magnet, the composition of which includes R, M, a remainder T and unavoidable impurities, wherein T contains Fe; R includes any one of Nd, Pr, La, Ce or Y or a combination of at least two; M includes any one of Cr, Co, Ni, Ga, Cu, Ti, Al, Zr or Nb or a combination of at least two.

[0009] The organizational structure of the NdFeB magnet includes: R2T14B main phase grains, thin layer grain boundary phase and triangular region grain boundary phase; the triangular region grain boundary phase includes a first grain boundary phase and a second grain boundary phase; the R content in the first grain boundary phase is less than 30at%, and the R content in the second grain boundary phase is greater than 30at%; wherein R is a non-heavy rare earth element; on any cross section of the magnet, the area of ​​the first grain boundary phase accounts for 65-86% of the total area of ​​the triangular region grain boundary phase.

[0010] The present invention enables more first grain boundary phases and second grain boundary phases to grow in the NdFeB magnet, so that the T element, especially the Fe element, in the magnet is more concentrated in the triangular grain boundary phase, thereby reducing the T element content in the thin-layer grain boundary phase, reducing the proportion of the ferromagnetic phase in the thin-layer grain boundary phase, and further improving the anti-demagnetization ability of the magnet, improving the temperature stability of the magnet, and enabling the magnet to maintain a high coercive force under high temperature conditions.

[0011] It is worth mentioning that when the amount of the first grain boundary phase generated is too small, resulting in the area of ​​the first grain boundary phase accounting for a small proportion of the total area of ​​the triangular zone grain boundary phase, it is difficult to make the R2T17 phase disappear, and the pinning effect on the main phase grains cannot be effectively exerted, making it difficult to consume too much iron in the triangular zone grain boundary phase, and ultimately the coercive force of the magnet cannot be improved.

[0012] Unlike the existing NdFeB magnets, the rare earth elements in the present invention do not contain heavy rare earth elements, including any one or a combination of at least two of Nd, Pr, La, Ce or Y, which can greatly reduce the production cost of NdFeB magnets. Typical but non-limiting combinations include a combination of Nd and Pr, a combination of La and Pr, a combination of Nd and La, a combination of Nd, Ce and Y, a combination of Nd, Pr, Ce and La, etc.

[0013] Specifically, M is any one of Cr, Co, Ni, Ga, Cu, Ti, Al, Zr or Nb, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of Ga and Cu, a combination of Co and Cr, a combination of Cu, Ga, Al and Ti, a combination of Zr, Al, Cu and Ga, a combination of Cu, Ga and Zr, and a combination of Ga, Cu and Co.

[0014] In the present invention, the R content in the first grain boundary phase is less than 30at%, for example, it can be 10at%, 13at%, 15at%, 17at%, 19at%, 21at%, 23at%, 25at%, 27at% or 29at%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0015] In the present invention, the first grain boundary phase is a gray grain boundary phase.

[0016] In the second grain boundary phase, R>30at%, for example, it can be 31at%, 32at%, 33at%, 34at%, 35at%, 36at%, 38at%, 40at%, 41at%, 44at%, 48at%, 50at%, 55at%, 57at%, 60at%, 62at% or 65at%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0017] On any cross-section of the magnet, the area of ​​the first grain boundary phase accounts for 65% to 86% of the total area of ​​the grain boundary phase in the triangular region, for example, it can be 65%, 66%, 67%, 68%, 69%, 70%, 72%, 74%, 75%, 77%, 78%, 80%, 83%, 85% or 86%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0018] Optionally, the T content in the first grain boundary phase is 60~80at%, for example, it can be 60at%, 63at%, 65at%, 67at%, 69at%, 72at%, 74at%, 76at%, 78at% or 80at%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0019] Optionally, the content of M in the second grain boundary phase is 5~20at%, for example, it can be 5at%, 7at%, 9at%, 10at%, 12at%, 14at%, 15at%, 17at%, 19at% or 20at%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0020] Optionally, the content of T in the second grain boundary phase is 20~60at%, for example, it can be 20at%, 25at%, 30at%, 36at%, 40at%, 43at%, 45at%, 47at%, 49at%, 52at%, 54at%, 56at%, 58at% or 60at%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0021] Optionally, on any cross-section of the magnet, the area of ​​the second grain boundary phase accounts for 10% to 30% of the total area of ​​the grain boundary phase in the triangular region, for example, it can be 10%, 13%, 15%, 17%, 19%, 22%, 24%, 26%, 28% or 30%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0022] Since the second grain boundary phase and the first grain boundary phase jointly consume iron in the triangular grain boundary phase, the present invention further prefers that the area ratio of the second grain boundary phase is within the above-mentioned range, which can better promote the disappearance of the R2T17 phase, thereby being sufficient to consume excessive iron in the triangular grain boundary phase and improve the coercive force of the magnet. At the same time, it can avoid the situation where the area ratio of the second grain boundary phase is too large, which leads to a reduction in the volume ratio of the main phase grains, further reducing the remanence of the magnet, and a decrease in the magnet density efficiency, resulting in a decrease in the mechanical properties of the magnet.

[0023] The NdFeB magnet further contains B, and the content of B in the NdFeB magnet is 0.82-0.9wt%, for example, 0.82wt%, 0.83wt%, 0.84wt%, 0.85wt%, 0.86wt%, 0.87wt%, 0.88wt% or 0.9wt%, etc., but is not limited to the listed values, and other values ​​not listed in the range are also applicable, preferably 0.835-0.87wt%;

[0024] In the present invention, the B content is less than 0.82wt%, and the R2T17 phase is generated, which cannot improve the coercive force of the magnet. When the B content is greater than 0.9wt%, the amount of the first grain boundary phase generated is reduced, making it difficult to consume too much iron in the triangular region grain boundary phase, making it difficult to improve the magnet's anti-demagnetization ability and to ensure that the magnet can maintain a high coercive force under high temperature conditions.

[0025] Optionally, the Ga content in the NdFeB magnet is 0.3~0.8wt%, for example, it can be 0.3wt%, 0.36wt%, 0.42wt%, 0.47wt%, 0.53wt%, 0.58wt%, 0.64wt%, 0.69wt%, 0.75wt% or 0.8wt%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable, preferably 0.45~0.7wt%.

[0026] In the present invention, the Ga content is less than 0.3wt%, the amount of the first grain boundary phase and the second grain boundary phase generated is too small, it is difficult to make the R2T17 phase disappear, and thus it is difficult to consume too much iron in the triangular region grain boundary phase, and it is difficult to further improve the coercive force of the magnet; the Ga content is greater than 0.8wt%, due to the presence of unnecessary Ga, the main phase ratio is reduced, the remanence is reduced, and the comprehensive magnetic properties are reduced.

[0027] Optionally, the Cu content in the NdFeB magnet is 0.1-0.5wt%, for example, it can be 0.1wt%, 0.15wt%, 0.19wt%, 0.24wt%, 0.28wt%, 0.33wt%, 0.37wt%, 0.42wt%, 0.46wt% or 0.5wt%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable, preferably 0.1-0.3wt%.

[0028] In the present invention, the Cu content is less than 0.1wt%, and when the amount of the second grain boundary phase generated is too small, too much iron cannot be consumed in the triangular region grain boundary phase, making it difficult to obtain a magnet with high coercivity and high temperature stability.

[0029] Optionally, the R content in the NdFeB magnet is 31~34wt%, for example, it can be 31wt%, 31.4wt%, 31.7wt%, 32wt%, 32.4wt%, 32.7wt%, 33wt%, 33.4wt%, 33.7wt% or 34wt%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0030] Optionally, the total content of M in the NdFeB magnet is 0.01~4wt%, for example, it can be 0.01wt%, 0.46wt%, 0.9wt%, 1.34wt%, 1.79wt%, 2.23wt%, 2.67wt%, 3.12wt%, 3.56wt% or 4wt%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable, preferably 1.1~2.7wt%.

[0031] In a second aspect, the present invention provides a method for preparing the NdFeB magnet according to the first aspect, the preparation method comprising:

[0032] Alloy powder is prepared according to the composition of NdFeB magnet; the alloy powder is compacted under magnetic field orientation to obtain a compact; the compact is sequentially sintered, aged and cooled after aging to obtain the NdFeB magnet; wherein the aging treatment includes a first aging treatment and a second aging treatment performed sequentially, the temperature of the first aging treatment is 700-845°C; and / or the temperature of the second aging treatment is 480-550°C.

[0033] The temperature of the first aging treatment is 700-845°C, for example, it can be 700°C, 717°C, 734°C, 750°C, 767°C, 784°C, 800°C, 817°C, 834°C or 845°C, but is not limited to the listed values, and other values ​​not listed in the range are also applicable. The holding time is 2-4h, for example, it can be 2h, 2.3h, 2.5h, 2.7h, 2.9h, 3.2h, 3.4h, 3.6h, 3.8h or 4h, but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0034] The temperature of the second aging treatment is 480-550°C, for example, 480°C, 488°C, 496°C, 504°C, 512°C, 519°C, 527°C, 535°C, 543°C or 550°C, but is not limited to the listed values, and other values ​​not listed in the range are also applicable. The holding time is 1-5h, for example, 1h, 1.5h, 1.9h, 2.4h, 2.8h, 3.3h, 3.7h, 4.2h, 4.6h or 5h, but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0035] The present invention sets the temperatures of the first aging treatment and the second aging treatment within the above range. Since the grain boundary phase composition of the magnet after sintering and cooling is uneven and the liquid phase content is high, the temperature range of the first aging treatment can promote the flow of the liquid phase and the uniform distribution inside the magnet without affecting the main phase grains, and construct a liquid phase network with uniform composition, which serves as a good basis for the subsequent intercrystalline reaction to form the first grain boundary phase and the second grain boundary phase. When the temperature of the first aging treatment is low, the uneven grain boundary phase composition inside the magnet after sintering and cooling may induce intercrystalline reaction, resulting in excessive enrichment of the first grain boundary phase in one place, which reduces the uniformity of the distribution of the first grain boundary phase and affects the consistency of the magnet. In addition, it will reduce the proportion of the first grain boundary phase and the second grain boundary phase formed by the subsequent intercrystalline reaction, and reduce the content of T elements (such as Fe) consumed in the grain boundary phase of the triangular region. When the temperature of the first aging treatment is high, the main phase grains inside the magnet participate in the reaction. Due to the sintering and cooling, the main phase grains inside the magnet participate in the reaction. The liquid phase inside the magnet after aging is unevenly distributed, the melting points of various regions inside are different, and the proportions of the main phase grains participating in the reaction are different, resulting in reduced consistency of the magnet. Due to the participation of the main phase grains in the reaction, it cannot be guaranteed that the subsequent intergranular reaction will form a limited proportion of the first grain boundary phase and the second grain boundary phase, which affects the iron consumption in the triangular region grain boundary phase. At the same time, the participation of the main phase grains in the reaction further increases the iron content of the grain boundary phase, affecting the overall demagnetization coupling effect of the magnet; when the temperature of the second aging treatment is low, the proportion of the first grain boundary phase with high iron content cannot be guaranteed, which affects the consumption of iron content in the triangular region grain boundary phase and cannot improve the coercive force of the magnet. When the temperature of the second aging treatment is high, it will promote the generation of a larger proportion of rare earth-rich phases and consume more rare earth elements R. In addition, it leads to a reduction in the generation of the first grain boundary phase and the second grain boundary phase, reduces the proportion of the first grain boundary phase and the second grain boundary phase, and reduces the iron content consumed in the triangular region grain boundary phase, which is not conducive to improving the high temperature stability of the magnet.

[0036] In the present invention, the thin layer grain boundary phase refers to the grain boundary phase formed between two adjacent main phase grains; the triangular region grain boundary phase refers to the grain boundary phase surrounded by three or more main phase grains.

[0037] Optionally, the preparation of the alloy powder includes: crushing alloy flakes with hydrogen and then jet milling to obtain alloy powder.

[0038] Optionally, the alloy flakes are obtained by cooling the raw materials after smelting, and the smelting temperature is 1400~1600℃, for example, it can be 1400℃, 1420℃, 14450℃, 1460℃, 1480℃, 1510℃, 1530℃, 1550℃, 1570℃ or 1600℃, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0039] Optionally, the particle size D50 of the alloy powder is 2~4μm, for example, it can be 2μm, 2.3μm, 2.5μm, 2.7μm, 2.9μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm or 4μm, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0040] Optionally, the magnetic field strength of the magnetic field orientation is 1.8~2.3T, for example, it can be 1.8T, 1.9T, 2T, 2.1T, 2.2T or 2.3T, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0041] Optionally, the sintering is vacuum sintering.

[0042] Optionally, the sintering temperature is 950~1050℃, for example, it can be 950℃, 960℃, 970℃, 980℃, 995℃, 1000℃, 1010℃, 1020℃, 1030℃ or 1050℃, but is not limited to the listed values, and other values ​​not listed in the range are also applicable, and / or, the sintering time is 5~15h, for example, it can be 5h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0043] Optionally, the sintering atmosphere is a vacuum condition or an argon atmosphere, and the vacuum degree of the vacuum atmosphere is 10 -5 ~10 -2 Pa, for example, can be 10 -5 Pa, 10 -4 Pa, 10 -3 Pa or 10 -2 Pa, etc., the gas pressure of the argon atmosphere is 5~20 kPa, for example, it can be 5 kPa, 7 kPa, 9 kPa, 10 kPa, 12 kPa, 14 kPa, 15 kPa, 17 kPa, 19 kPa or 20 kPa, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0044] Optionally, the density of the blank obtained after sintering is 7.5-7.8 g / cm 3 , for example, it can be 7.5g / cm 3 、7.54g / cm 3 、7.57g / cm 3 、7.6g / cm 3 、7.64g / cm 3 、7.67g / cm 3 , 7.7g / cm 3, 7.74g / cm 3 , 7.77g / cm 3 or 7.8g / cm 3 The above values ​​are not limited to the above values, and other values ​​not listed in the above values ​​are also applicable.

[0045] Optionally, the holding time of the first aging treatment is 2 to 4 hours, for example, it can be 2 hours, 2.3 hours, 2.5 hours, 2.7 hours, 2.9 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, and other values ​​not listed in this range are also applicable.

[0046] Optionally, the holding time of the second aging treatment is 1 to 5 hours, for example, it can be 1 hour, 1.5 hours, 1.9 hours, 2.4 hours, 2.8 hours, 3.3 hours, 3.7 hours, 4.2 hours, 4.6 hours or 5 hours, but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0047] Optionally, the cooling rate of the post-aging cooling is greater than 6.6°C / min, for example, it can be 6.7°C / min, 7.1°C / min, 7.5°C / min, 7.8°C / min, 8.2°C / min, 8.6°C / min, 8.9°C / min, 9.3°C / min, 9.7°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0048] The preparation method of the present invention adopts a secondary aging treatment process matched with a rapid cooling rate of >6.6°C / min, which can enable uniform intergranular reaction inside the magnet, promote the effective generation of the first grain boundary phase and the second grain boundary phase, and make the R2T17 phase disappear. Rapid cooling using the above cooling rate can maintain the consistent structure of the first grain boundary phase and the second grain boundary phase, thereby achieving the effect of improving the coercive force and high-temperature stability of the magnet.

[0049] In a third aspect, the present invention provides an application of the NdFeB magnet described in the first aspect and / or the NdFeB magnet prepared by the preparation method of the NdFeB magnet described in the second aspect in the automotive industry, electronic products, wind power, elevators, industrial robots or aerospace.

[0050] The NdFeB magnet provided by the present invention can be widely used in various fields due to its excellent coercive force, remanence and high-temperature stability, and has broad application prospects.

[0051] Compared with the prior art, the present invention has at least the following beneficial effects:

[0052] (1) The NdFeB magnet provided by the present invention generates a larger proportion of the first grain boundary phase and the second grain boundary phase in the triangular region grain boundary phase of the magnet, so that the T element, especially the Fe element, in the magnet is more concentrated in the triangular region grain boundary phase, reducing the content of the T element, especially the Fe element, in the thin layer grain boundary phase, so that the proportion of the ferromagnetic phase in the thin layer grain boundary phase is reduced, thereby improving the anti-demagnetization ability of the magnet and improving the temperature stability of the magnet, so that the magnet maintains a high coercive force under high temperature conditions. Specifically, the Br of the magnet is above 13.16 kGs, the Hcj is above 20.06 kOe, and the absolute value of the Hcj temperature coefficient α% / ℃ at 20-180℃ is within 0.565;

[0053] (2) The method for preparing the NdFeB magnet provided by the present invention further adjusts the contents of B, Ga and Cu within a specific range so that the microstructure of the NdFeB magnet includes: R2T14B main phase grains, the first grain boundary phase and the second grain boundary phase, thereby achieving effective preparation of the corresponding microstructure;

[0054] (3) The method for preparing the NdFeB magnet provided by the present invention can prepare the NdFeB magnet having the first grain boundary phase and the second grain boundary phase with a high Fe content by adopting aging treatment and controlling the cooling rate after aging treatment within a specific range, thereby significantly improving the high temperature stability of the NdFeB magnet and improving the anti-demagnetization ability of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a SEM image of the NdFeB magnet prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0057] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0058] Example 1

[0059] This embodiment provides a NdFeB magnet, wherein the composition of the NdFeB magnet includes 32.7wt% of R, 1.5wt% of M, 0.845wt% of B, and the remainder T and unavoidable impurities;

[0060] Wherein the R is Nd and Pr; the T is Fe and Co; and the M includes 0.18 wt % of Cu and 0.6 wt % of Ga.

[0061] This embodiment also provides a method for preparing the above-mentioned NdFeB magnet, and the preparation method comprises the following steps:

[0062] (1) The raw materials are as described above for the composition of the NdFeB magnets. The raw materials are melted at 1500°C and then cooled to obtain alloy quick-solidification sheets;

[0063] (2) The alloy quick-setting sheet in step (1) is subjected to hydrogen crushing and then finely ground by air jet milling to obtain an alloy powder with an average particle size D50 of 3 μm, wherein the hydrogen absorption pressure of the hydrogen crushing is 0.4 MPa, the dehydrogenation temperature is 550°C, and the grinding pressure of the air jet mill is 0.68 MPa;

[0064] (3) pressing the alloy powder prepared in step (2) under nitrogen protection and magnetic field orientation with a magnetic field strength of 2.0 T to obtain a compact;

[0065] (4) The compact obtained in step (3) is placed in a vacuum sintering furnace and sintered at 1000°C for 10 h. The vacuum degree is controlled at 10 -3 Pa, the compact is densified to obtain a blank, the density of which is 7.7 g / cm 3 ;

[0066] (5) The blank of step (4) is subjected to a first aging treatment at a temperature of 830°C and a holding time of 3 h, and a second aging treatment at a temperature of 520°C and a holding time of 1.2 h, and then subjected to post-aging cooling at a cooling rate of 15°C / min to obtain the NdFeB magnet.

[0067] The prepared NdFeB magnets were subjected to microstructural tests, see Figure 1 The test results show that NdFeB magnets include main phase grains and grain boundary phases, among which the grain boundary phases include thin layer grain boundary phases and triangular region grain boundary phases, and the triangular region grain boundary phases contain the first grain boundary phase ( Figure 1 Medium gray grain boundary phase, labeled A) and second grain boundary phase ( Figure 1 The bright white grain boundary phase is labeled B).

[0068] The distribution of the first grain boundary phase and the second grain boundary phase in the triangular region grain boundary phase in the NdFeB magnet prepared in Example 1 was statistically calculated using image analysis software (image proplus). The area of ​​the first grain boundary phase accounted for 70% of the total area of ​​the triangular region grain boundary phase in the cross section, and the area of ​​the second grain boundary phase accounted for 16% of the total area of ​​the triangular region grain boundary phase in the cross section.

[0069] Example 2

[0070] Referring to the preparation method of Example 1, the difference from Example 1 is that the composition of the NdFeB magnet includes 32.2wt% of R, 1.3wt% of M, 0.845wt% of B, and the remainder T and unavoidable impurities; wherein the R is Nd and Pr; the T is Fe; and the M includes 0.15wt% of Cu and 0.58wt% of Ga.

[0071] The second aging treatment temperature is 500°C.

[0072] Example 3

[0073] This embodiment provides a neodymium iron boron magnet, and the composition of the neodymium iron boron magnet is the same as that of embodiment 2. The difference between the preparation method and embodiment 2 is:

[0074] The temperature of the first aging treatment was 820°C and the time was 4 h. The temperature of the second aging treatment was 510°C and the time was 1.3 h. The cooling rate after aging was 7°C / min.

[0075] The rest are the same as those in Example 2 and will not be described again.

[0076] Example 4

[0077] This embodiment provides a neodymium iron boron magnet, and the composition of the neodymium iron boron magnet is the same as that of embodiment 1. The difference between the preparation method and embodiment 1 is:

[0078] The first aging treatment was performed at a temperature of 845°C for 2 h, and the second aging treatment was performed at a temperature of 480°C for 2.5 h.

[0079] The rest are the same as in Example 1 and will not be described again.

[0080] Example 5

[0081] This embodiment provides a neodymium iron boron magnet, and the composition of the neodymium iron boron magnet is the same as that of embodiment 1. The difference between the preparation method and embodiment 1 is:

[0082] The first aging treatment was performed at a temperature of 700°C for 3 h, and the second aging treatment was performed at a temperature of 550°C for 1 h.

[0083] The rest are the same as in Example 1 and will not be described again.

[0084] Example 6

[0085] Referring to the preparation method of Example 1, the difference from Example 1 is that the B content in the composition of the NdFeB magnet is 0.88wt%.

[0086] Comparative Example 1

[0087] This comparative example provides a neodymium iron boron magnet, which is the same as Example 1 except that the first stage aging treatment temperature is 860° C., and will not be described in detail here.

[0088] Comparative Example 2

[0089] This comparative example provides a neodymium iron boron magnet, which is the same as Example 1 except that the second aging treatment temperature is 470° C., and will not be described again.

[0090] Comparative Example 3

[0091] This comparative example provides a neodymium iron boron magnet. Except that the second aging treatment temperature of the neodymium iron boron magnet is 560° C., the rest is the same as that of Example 1, which will not be described again.

[0092] After preparing the sample of the magnet of Example 1, a scanning electron microscope was used to take a cross-sectional image, and the obtained SEM image was as follows: Figure 1 As shown, the observation plane is perpendicular to the orientation direction of the magnet. The grain boundary phase in the triangular region of the magnet in Example 1 includes a first grain boundary phase (gray grain boundary phase) and a second grain boundary phase (white highlighted grain boundary phase). The first grain boundary phase and the second grain boundary phase can be distinguished based on the electron backscattered image, and the contrast of the backscattered electron image of the second grain boundary phase is slightly higher than that of the first grain boundary phase.

[0093] The distribution of the first grain boundary phase (gray grain boundary phase) and the second grain boundary phase (white highlighted grain boundary phase) in the triangular region grain boundary phase of the magnet can be statistically analyzed using image pro plus image analysis software: randomly select any 5 or more sections in the magnet for analysis, wherein more than 5 50μm×50μm areas are randomly selected for each section, and the area ratio of the first grain boundary phase to the triangular region grain boundary phase in each area of ​​each section is tested and the average value is taken as the area ratio of the first grain boundary phase to the triangular region grain boundary phase of the section, and then the area ratio of the first grain boundary phase to the triangular region grain boundary phase of all sections is calculated, and the results are shown in Table 1; the area ratio of the second grain boundary phase to the triangular region grain boundary phase of all sections is the same as the statistical method of the area ratio of the first grain boundary phase to the triangular region grain boundary phase.

[0094] The NdFeB magnets prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were selected and tested by EDS energy spectrum analysis to test the atomic percentage of each element in the first grain boundary phase and the second grain boundary phase. The results are shown in Table 1.

[0095] The magnetic properties of the NdFeB magnets of Examples 1 to 6 and Comparative Examples 1 to 3 were tested using a BH plotter. The results are shown in Table 2.

[0096] Table 1

[0097]

[0098] Table 2

[0099]

[0100] From Table 1 and Table 2, we can see the following points:

[0101] (1) It can be seen from Examples 1 to 6 that the Br of the NdFeB magnet provided by the present invention is above 13.16 kGs, the Hcj is above 20.06 kOe, and the absolute value of the Hcj temperature coefficient α% / °C at 20-180°C is within 0.565, indicating that the present invention improves the anti-demagnetization ability of the magnet and enhances the temperature stability of the magnet;

[0102] (2) It can be seen from Example 1 and Comparative Examples 1 to 3 that the temperature of the first aging treatment in Comparative Example 1 is 860°C, which is too high, resulting in a low proportion of the first crystal interface to the area of ​​the triangular grain boundary phase, which is only 64%. The temperatures of the second aging treatment in Comparative Examples 2 and 3 are respectively too high or too low, which results in a low proportion of the first crystal interface to the area of ​​the triangular grain boundary phase, which is only 43% and 55%, respectively. Finally, the absolute values ​​of the 20-180°C Hcj temperature coefficient α% / °C of the NdFeB magnets in Comparative Examples 1 to 3 are as high as 0.582, 0.654 and 0.623, respectively, and the coercive force of the magnets in Comparative Examples 1 to 3 is significantly lower than that in Example 1. This shows that the area proportion of the first grain boundary phase to the triangular grain boundary phase is critical to the temperature stability of the magnet. The present invention can adjust the area proportion of the first grain boundary phase and the triangular grain boundary phase by adjusting the temperature of the aging treatment, thereby improving the temperature stability and magnetic properties of the magnet.

[0103] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A neodymium iron boron magnet, characterized in that: The composition of the NdFeB magnet includes R, M, the remainder T and inevitable impurities, wherein the T contains Fe; The R includes any one of Nd, Pr, La, Ce or Y or a combination of at least two thereof; The M includes any one of Cr, Co, Ni, Ga, Cu, Ti, Al, Zr or Nb, or a combination of at least two thereof; The organizational structure of the NdFeB magnet includes: R2T14B main phase grains, thin layer grain boundary phase and triangular region grain boundary phase; The triangular region grain boundary phase includes a first grain boundary phase and a second grain boundary phase; the R content in the first grain boundary phase is less than 30 at%, and the R content in the second grain boundary phase is greater than 30 at%; On any cross section of the magnet, the area of ​​the first grain boundary phase accounts for 65-86% of the total area of ​​the grain boundary phase in the triangular region; The T content in the first grain boundary phase is 60-80 at%; The content of T in the second grain boundary phase is 20-60at%.

2. The NdFeB magnet according to claim 1, characterized in that: The content of M in the second grain boundary phase is 5-20 at%; And / or, on any cross section of the magnet, the area of ​​the second grain boundary phase accounts for 10-30% of the total area of ​​the grain boundary phase in the triangular region.

3. The NdFeB magnet according to claim 1 or 2, characterized in that: The NdFeB magnet also contains B, and the content of B in the NdFeB magnet is 0.82-0.9wt%; And / or, the Ga content in the NdFeB magnet is 0.3-0.8wt%; And / or, the Cu content in the NdFeB magnet is 0.1-0.5wt%.

4. The NdFeB magnet according to claim 3, characterized in that: The Ga content in the NdFeB magnet is 0.45-0.7wt%; And / or, the B content in the NdFeB magnet is 0.835-0.87wt%.

5. The NdFeB magnet according to claim 4, characterized in that: The R content in the NdFeB magnet is 31-34wt%, and / or the total M content in the NdFeB magnet is 0.01-4wt%.

6. A method for preparing a NdFeB magnet according to any one of claims 1 to 5, characterized in that: The preparation method comprises: preparing alloy powder according to the composition of NdFeB magnet; The alloy powder is pressed and formed under magnetic field orientation to obtain a compact; The compact is sequentially sintered, subjected to aging treatment and cooled after aging to obtain the NdFeB magnet; Wherein, the aging treatment includes a first aging treatment and a second aging treatment performed sequentially, the temperature of the first aging treatment is 700-845°C; and / or the temperature of the second aging treatment is 480-550°C.

7. The preparation method according to claim 6, characterized in that: The preparation of the alloy powder comprises: crushing the alloy flakes with hydrogen and then jet milling them to obtain the alloy powder; And / or, the particle size D50 of the alloy powder is 2-4 μm; And / or, the magnetic field strength of the magnetic field orientation is 1.8~2.3T.

8. The preparation method according to claim 6 or 7, characterized in that: The sintering is vacuum sintering; the sintering temperature is 950-1050° C., and / or the sintering time is 5-15 hours; And / or, the sintering atmosphere is a vacuum condition or an argon atmosphere, and the vacuum degree of the vacuum condition is 10 -5 ~10 -2 Pa, the gas pressure of the argon atmosphere is 5~20kPa; And / or, the density of the blank obtained after sintering is 7.5-7.8 g / cm 3 .

9. The preparation method according to claim 6, characterized in that: The cooling rate of the post-aging cooling is > 6.6°C / min; And / or, the holding time of the first aging treatment is 2 to 4 hours; And / or, the holding time of the second aging treatment is 1 to 5 hours.

10. Application of a NdFeB magnet as claimed in any one of claims 1 to 5 and / or a NdFeB magnet as claimed in any one of claims 6 to 9 in the automotive industry, electronic products, wind power, elevators, industrial robots or aerospace.